Synthesis and Spectral Studies of Novel Co(II), Ni(II), Cu(II), Cd(II), and Fe(II) Metal Complexes with N-[5?-Amino-2,2?-bis(1,3,4-thiadiazole)-5-yl]-2-hydroxybenzaldehyde Imine (HL) - Turan, Nevin; Sekerci, Memet (Taylor & Francis Inc, 2009)
Co(II), Ni(II), Cu(II), Cd(II), and Fe(II) complexes with Schiff base derived from 2-amino-5-(2-amino-1,3,4-thiadiazolyl)-1,3,4-thiadiazole (1) and salicylaldehyde have been prepared. The ligand and its complexes have been characterized by IR, H-1 NMR spectra, elemental analyses, magnetic susceptibility, UV-Vis. and thermogravimetry-differential thermal analysis (TGA-DTA). The analytical data show 1: 2 metal-to-ligand ratio for Co(II), Ni(II), Cd(II), and Fe(II) and 2: 2 metal-to-ligand ratio for Cu( II) complexes. The suggested structures for the N-[5'-Amino-2,2'-bis(1,3,4-thiadiazole)-5-yl]-2-hydroxybenzaldehyde Imine (HL) complexes of Fe(II), Co(II), and Cd(II) are octahedral, for the Ni(II) complex is tetrahedral, and for the Cu(II) complex is square-planar
Keywords: 1,3,4-thiadiazole; salicylaldehyde; Schiff base and complexes